A companion to translation studies - Bermann, Sandra, 1947-; Porter, Catherine, 1941- (Hoboken : Wiley-Blackwell, 2014)
'This companion offers a wide-ranging introduction to the rapidly expanding field of translation studies, bringing together some of the best recent scholarship to present its most important current themes Features new work from well-known scholars Includes a broad range of geo-linguistic and theoretical perspectives Offers an up-to-date overview of an expanding field A thorough introduction to translation studies for both undergraduates and graduates Multi-disciplinary relevance for students with diverse career goals '--
'Multi-disciplinary relevance for students with diverse career goals'--
Includes index.
Keywords: Translating and interpreting -- Study and teaching (Higher).; Translating and interpreting -- Vocational guidance